Evaluating Capacity Development: Experiences from Research and Development Organizations around the World - Horton, Douglas; Alexaki, Anastasia; Bennett-Lartey, Samuel; Brice, Kim N.; Campilan, Dindo; Carden, Fred; Souza Silva, J. de; Le Thanh Duong; Khadar, Ibrahim; Maestrey Boza, Albina; Kayes Muniruzzaman, Imrul; Perez, Jocelyn; et al. (International Service for National Agricultural Research, 2003)
The international community is placing a growing emphasis on developing local capacity as the key to alleviating poverty and hunger in the developing world. Although ensuring the effectiveness of a capacity building effort requires appropriate use of evaluation, few organizations have implemented a system for monitoring or evaluating the changes taking place during organizational development. In January 2000, ISNAR began an ambitious Evaluating Capacity Development project, which aimed to improve capacity development efforts in research and development organizations through the use of evaluation. This book explains how the project used an action learning approach, bringing together people from various countries and different types of organizations. As they conducted six evaluation studies over the course of three years, project participants learned a great deal about capacity development and the process of evaluation. The authors use examples and lessons drawn from the evaluation studies as a basis for making more general conclusions regarding how capacity development efforts and evaluation can help organizations to achieve their missions.